Informatorische Methoden und Technologien im Fußball - Baca, A. (Österreichisches Journal für Sportmedizin, 2001)
Opportunities and limits relating to the use of information technology in soccer are discussed: - Digital video editing tools and interactive video systems enable the generation of powerful, didactically effective presentattions. - Modern computer-assisted game analysis systems do not omly allow to analyse individual players and the tactical behaviour of the whole team, but also to evaluate the kinematic characteristics such as running distances. The use of automatic tracking systems may reduce the expenditure for data acquisition considerably. Due to the frequent occurence of critical situations in soccer, modelling the game process is rather difficult. Data mining is a promising method to assist planning the strategy of a game. - The scientific usefulness of computer-graphical presentation tools is limited.